Implementing Strategic Environmental Assessment - Schmidt, Michael; Joao, Elsa.; Albrecht, Eike.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2005)
More countries are now using Strategic Environmental Assessment (SEA) than ever before. This timely and comprehensive Handbook describes the implementation of SEA in 18 countries around the world, as well as a critical analysis of different SEA methodologies. The Handbook starts by introducing key SEA principles and the legal requirements of the new European SEA Directive (which became law in 2004). It then describes the implementation of SEA in 11 European Union countries, as well as the USA, Canada and New Zealand. This is contrasted with SEA requirements of four developing countries. The Handbook explores public participation issues and the wide-range of SEA methodologies used in terms of resources (soils, water and biodiversity) and sectors of activity (transport, agriculture, waste management and industry). The Handbook concludes with a discussion on best practice, capacity building and the future of SEA.
Key Principles of SEA -- Purpose and Background of the European SEA Directive -- Legal Context of the SEA Directive — Links with other Legislation and Key Procedures -- Transposition of the SEA Directive into National Law — Challenges and Possibilities -- Some Legal Problems of Implementing the SEA Directive into Member States’ Legal Systems -- Current SEA Practice in England -- Implementing SEA in Germany -- Implementing SEA in Italy — The Case of the Emilia Romagna Region -- First Experiences with Implementing SEA Legislation in Flanders (Belgium) -- Implementing SEA in Austria -- Implementing SEA in Finland — Further Development of Existing Practice -- Problems of a Minimalist Implementation of SEA — The Case of Sweden -- National Strategy for the Implementation of SEA in the Czech Republic -- Developments of SEA in Poland -- Experiences with SEA in Latvia -- Implementing SEA in Estonia -- Improved Decision-Making through SEA — Expectations and Results in the United States -- SEA in Canada -- SEA of Plan Objectives and Policies to Promote Sustainability in New Zealand -- The Need for SEA in Kenya -- SEA for Water Resource Management in Ghana -- SEA in Ukraine -- Importance of SEA in China — The Case of Three Gorges Dam Project -- Tools for SEA -- Methodological Approaches to SEA within the Decision-Making Process -- Strategic Level Cumulative Impact Assessment -- Handling Transboundary Cumulative Impacts in SEA -- Cultural Integrity as a Criterion of SEA -- Requirements and Methods for Public Participation in SEA -- Public Participation for SEA in a Transboundary Context -- Developing Quantitative SEA Indicators Using a Thermodynamic Approach -- A Structural and Functional Strategy Analysis for SEA -- Soil Resources and SEA -- Towards the Implementation of SEA — Learning from EIA for Water Resources -- Links between the Water Framework Directive and SEA -- Assessing Biodiversity in SEA -- Biodiversity Programmes on Global, European and National Levels Related to SEA -- Co-ordination of SEA and Landscape Planning -- Urban Planning and SEA -- SEA in Transport Planning in Germany -- SEA for Agricultural Programmes in the EU -- SEA of Waste Management Plans — An Austrian Case Study -- Mining Industry and SEA — An Example in Turkey -- Capacity-Building and SEA -- A Critique of SEA from the Point of View of the German Industry -- Best Practice Use of SEA — Industry, Energy and Sustainable Development -- SEA Outlook — Future Challenges and Possibilities.
Keywords: Environmental law; Environmental policy; International environmental law; Environmental economics; Environmental Law/Policy/Ecojustice.; International Environmental Law; Environmental Economics